PRINCIPLES OF FINANCIAL MANAGEMENT: OPERATIONAL LEVERAGE AND FINANCIAL LEVERAGE - Muhammad Haekal Yunus; Ni Komang Septia Noriska; Sri Hartati; Devia Septyani (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Understanding and mastering the principles of financial management is not only the key to success in running a business, but also very vital in our personal lives. In this world full of uncertainty, the ability to manage finances wisely can determine financial stability in the future. With good financial management, companies can allocate expenditure and income funds appropriately. Understanding the principles of operational leverage and financial leverage is very important in financial management. Both can be used to maximize profits, but also carry risks that need to be managed properly. With the right strategy, companies can use leverage to achieve their financial goals. In financial management, leverage is an important concept used to increase the company's profit potential. The utilization of fixed costs in the business's cost structure is associated with operational leverage. Leverage in finance is the process of using debt to fund a company's operations and assets. The performance of the business as a whole may be impacted by these two interrelated forms of leverage. Nevertheless, the amalgamation of these two categories of leverage can also increase risk, so financial managers need to be careful in planning the company's cost and financing structure.